Mimicry of erythropoietin by a nonpeptide molecule - Qureshi, Sajjad A. (The National Academy of Sciences, 1999)
Erythropoietin (EPO) controls the proliferation and differentiation of erythroid progenitor cells into red blood cells. EPO induces these effects by dimerization of the EPO receptors (EPOR) present on these cells. To discover nonpeptide molecules capable of mimicking the effects of EPO, we identified a small molecule capable of binding to one chain of EPOR and used it to synthesize molecules capable of inducing dimerization of the EPOR. We first identified compound 1 (N-3-[2-(4-biphenyl)-6-chloro-5-methyl]indolyl-acetyl-l-lysine methyl ester) by screening the in-house chemical collection for inhibitors of EPO binding to human EPOR and then prepared compound 5, which contains eight copies of compound 1 held together by a central core. Although both compounds inhibited EPO binding of EPOR, only compound 5 induced dimerization of soluble EPOR. Binding of EPO to its receptor in cells results in activation of many intracellular signaling molecules, including transcription factors like signal transducer and activator of transcription (STAT) proteins, leading to growth and differentiation of these cells. Consistent with its ability to induce dimerization of EPOR in solution, compound 5 exhibited much of the same biological activities as EPO, such as (i) the activation of a STAT-dependent luciferase reporter gene in BAF3 cells expressing human EPOR, (ii) supporting the proliferation of several tumor cell lines expressing the human or mouse EPOR, and (iii) the in vitro differentiation of human progenitor cells into colonies of erythrocytic lineage. These data demonstrate that a nonpeptide molecule is capable of inducing EPOR dimerization and mimicking the biological activities of EPO.